Information and communications technologies use by medical sciences’ students - Rafaela Nayibe Curi Mendoza; Nayibe Reytor Curi (Medisur)
Foundation: there are deficiencies regarding the proper management of digital media by medical science students; as well as a need for the corresponding institutions to recognize the importance of media education in their curricular training. Objective: characterize the information and communications technologies use by medical sciences students. Methods: a descriptive, cross-sectional study was carried out. From the universe of 73 students of the Short Cycle Technicians, a sample of 30 students from the first year of the Short Cycle Higher Technician in Clinical Analysis and Transfusion Medicine, belonging to the Victoria de Girón Faculty, were selected from 2022 to 2023 academic year. The information was obtained through a questionnaire applied to the participants. Results: 100% of the students reported that they accessed the internet; most of them (86.6%) by a cell phone. 56.6% expressed that they connect more than 8 hours a day. 26.7% used it in academic tasks. 93.3% used social networks: Facebook for 100% of them; 93.3% WhatsApp. The most used content was music (100%). Conclusions: the Internet connection prolonged time by students, and the use of social networks in consumption and production of content unrelated to academic activity and sometimes inappropriate, indicate the importance of media education for adequate training in the new technologies use.